Rapid Assessment of Personnel and Equipment Availability in Sports Medicine Services - Bunga Listia Paramita; Ede Surya Darmawan (Media Kesehatan Masyarakat Indonesia, 2021)
Hospitals that already have sports medicine services need to constantly make improvements and innovations to ensure the implementation of complete services. This study aims to explain the description of the availability of personnel and equipment at a hospital in Jakarta and the extent of their suitability based on literature studies in order to support sports medicine services. This research method is descriptive qualitative with triangulation methods, namely observation, indepth interviews with 4 key informants, review of hospital documents, and is equipped with a literature study to match the personnel and equipment available with those found in the literature study. This research is located at a hospital in Jakarta, which runs from November 3, 2020 to December 1, 2020. The results show that the hospital has sufficiently complete personnel and only needs to complete the availability of sports psychologists. Meanwhile, nutritionists and dentists can ask for the willingness of the staff in the hospital to join as a sports medicine team. For podiatrists and health education providers, their role can be carried out by other personnel in the field of sports medicine who have similar competencies. The equipment owned by that hospital is also quite complete, but it should be equipped with MRI, as well as tools that have become gold standards, including CPET and DXA Scan. The fulfillment of these personnel and equipment should be a development plan for sports medicine services in stages in the future.